DIAGNOSIS AND RECOMMENDATION INTEGRATED SYSTEM (DRIS) A BETTER APPROACH TO COCONUT NUTRITION - T.I. Mathewkutty; E. Tajuddin (International Coconut Community Journal, 1996)
Coconut is grown in more than 90 countries in the world and India occupies the third position with an area of 1.63 million hectares and a production of 12355 million nuts [Anon(a)1993‑94]. The crop makes a significant contribution to the national economy to the extent of Rs. 4,000 crores with an annual export earning of Rs. 126 crores [Anon (b) 1993‑94] per year which is much below its potential of more than 100 nuts per palm per year. Lack of adequate and proper management of nutrients is one of the reasons for this low productivity.